2019
DOI: 10.1180/mgm.2019.72
|View full text |Cite
|
Sign up to set email alerts
|

Tourmaline from the Solnechnoe tin deposit, Khabarovsk Krai, Russia

Abstract: Tourmaline from the Solnechnoe hydrothermal granitoid-related tin deposit in the Khabarovsk Krai, Russian Far East has been studied with electron microprobe, infrared and Mössbauer spectroscopy. Tourmaline formed in three distinct stages with different types of chemical substitution. Tourmaline from the first unmineralised stage is classified as dravite or schorl, which could be enriched locally in Ca, the X-site vacancy and F. This tourmaline is characterised by the Fe ↔ Mg and X vacancy + Al ↔ Na + Fe substi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…Our data on tin-tourmaline and tin-pyroxene (Tab. 2), data on tin-tourmaline (Baksheev et al 2020), and coexisting tin-free melilite and tin-enriched pyroxene (Butler 1978), suggest that Sn 4+ occupies octahedral sites in the tourmaline and pyroxene crystal structures. Baksheev et al (2020) pointed out that, despite the Si content variation in Sn-bearing schorl, no correlation between Si and Sn was found and suggested the substitution scheme for the Sn-bearing schorl as follows: (Baksheev et al 2020).…”
Section: Tin-enriched Tourmalinesmentioning
confidence: 97%
See 2 more Smart Citations
“…Our data on tin-tourmaline and tin-pyroxene (Tab. 2), data on tin-tourmaline (Baksheev et al 2020), and coexisting tin-free melilite and tin-enriched pyroxene (Butler 1978), suggest that Sn 4+ occupies octahedral sites in the tourmaline and pyroxene crystal structures. Baksheev et al (2020) pointed out that, despite the Si content variation in Sn-bearing schorl, no correlation between Si and Sn was found and suggested the substitution scheme for the Sn-bearing schorl as follows: (Baksheev et al 2020).…”
Section: Tin-enriched Tourmalinesmentioning
confidence: 97%
“…% SnO 2 (Drivenes 2021); in Solnechnoe in Russia -1.02 wt. % SnO 2 ; (Baksheev et al 2020); in Pridorozhnoe in 3-1; Tab. 2), we found out that a pressure increase influences the titanium content negatively in our synthetic tourmalines.…”
Section: Tin-enriched Tourmalinesmentioning
confidence: 99%
See 1 more Smart Citation
“…The data in Bosi et al (2017) plot from oxy-schorl towards dravite composition, concerning Al-Fe-Mg, until it reaches the line connecting oxydravite and povondraite, which the data plot neatly along towards povondraite. The data in this study differ from those reviewed in Bosi et al (2017) in that the change in the direction of the trend towards Fe-rich compositions happens before the oxy-dravite-povondraite line and that the exchange vector controlling the composition with increasing Fe involves Mg, although as Bosi et al (2017) concluded, there is no evidence for a direct solid solution between oxy-schorl and bosiite or povondraite (e.g., a Mg 2 Fe 1 Al -3 exchange vector) Previously suggested substitution schemes for Sn in tourmaline include X Na + + YZ Fe 2+ + YZ Sn 4+ ↔ X Ca 2+ + YZ Mg 2+ + YZ Al 3+ , 2 XY Al 3+ ↔ YZ Sn 4+ + YZ Mg 2+ , YZ Al 3+ + VW OH -↔ YZ Sn 4+ + VW O 2-, and 2 YZ Mg 2+ ↔ YZ Sn 4+ + YZ ☐ (Baksheev et al 2020;Vereshchagin et al 2022). The Sn-rich tourmalines in this study are Fe-rich, and the latter three substitution reactions were derived from synthesized dravite.…”
Section: Incorporation Of Sn Into the Tourmaline Structurementioning
confidence: 99%
“…Tourmaline is stable over the wide range of pressure-temperature conditions, from lowtemperature hydrothermal to magmatic and high-pressure metamorphic (Henry and Dutrow 1996; https://doi.org/10.1180/mgm.2022.104 Published online by Cambridge University Press Selway et al, 1999;Marks et al, 2013;Baksheev et al, 2019) and therefore is a good indicator of the mineral-forming environment. The major and trace element composition, substitution mechanisms, and spectroscopic features may help to understand the fractionation degree and the evolution of a pegmatite melt in general (Čerńy et al, 1985;Jolliff et al, 1986;Tindle et al, 2002;Roda-Robles et al, 2004).…”
Section: Introductionmentioning
confidence: 99%